Maçã 'Eva' orgânica submetida a aplicação pós-colheita de cloreto de cálcio - Vieites, Rogério Lopes [UNESP]; Soares, Laís Peixoto da Rocha [UNESP]; Daiuto, Érica Regina [UNESP]; Mendonça, Veridiana Zocoler de [UNESP]; Furlaneto, Karina Aparecida [UNESP]; Fujita, Erika [UNESP] (Revista Nativa, 2014)
The quality of organic apples 'Eva' subjected to the postharvest treatment with calcium chloride was evaluated. The experiment consisted of the fruits immersion in different calcium chloride concentrations (1.0%, 1.5%, 2.0% and 2.5%) for 15 minutes and one control (dipping in water). The fruits were stored to the temperature of 0±1oC and relative humidity of 60 ± 6% for 20 days, being the accomplished evaluations every 5 days. The fruits evaluation were: weigth loss, respiratory activity, peel and pulp coloration, hidrogenionic potential (pH), tritable acidity (AT), soluble solids (SS), maturation index (IM), total phenolics content and antioxidant activity by DPPH. The smallest weight loss were in the fruits control (conventional cultivate and without application CaCl2), where in the end of the 20 days of storage they presented losses of 2.64%. Already the control with organic fruits, the largest percentage of weight loss was observed arriving to 8.5% in the end of the storage period. Application of calcium chloride in the organic apples provided less intense production of CO2 and delay in the pick climateric in relation to the organic control fruits. The quality parameters (SS, pH, AT and IM) it doesn't influenced by the different concentrations of calcium chloride applied. The total phenolic content didn't suffer influence by the applied calcium chloride concentrations, but they altered during the experimental period.

Avaliou-se a qualidade de maçãs 'Eva' de cultivo orgânico submetidas ao tratamento pós colheita com cloreto de cálcio. Os frutos forma imersos por 15 minutos em CaCl2, constituindo os tratamentos controle (imersão em água); CaCl2 à 1%; CaCl2 à 1,5%; CaCl2 à 2,0%; CaCl2 à 2,5%.Os frutos foram armazenados à temperatura de 0±1oC e umidade relativa de 60 ± 6% durante 20 dias, sendo as avaliações realizadas a cada 5 dias. Os frutos foram avaliados quanto a perda de massa, atividade respiratória, coloração da casca e polpa, potencial hidrogeniônico (pH), acidez titulável (AT), sólidos solúveis (SS), índice de maturação (IM), compostos fenólicos totais e atividade antioxidante por DPPH. As menores perdas de massa foram nos frutos controle (cultivo convencional e sem aplicação CaCl2), onde no final dos 20 dias de armazenamento apresentavam perdas de 2,64%. Já o controle com frutos orgânicos, foi observado a maior porcentagem de perda de massa fresca chegando a 8,5% no final do período de armazenamento. Aplicação de cloreto de cálcio nas maçãs orgânicas proporcionou produção menos intensa de CO2 e atraso no pico climatérico em relação aos frutos orgânicos controle. Os parâmetros de qualidade (SS, pH, AT e IM) não foram influenciados pelas diferentes doses de cloreto de cálcio aplicadas. O teor de compostos fenólicos não sofreram influência da dose aplicada de cloreto de cálcio, mas alteraram no decorrer do período experimental.
Organic apple 'Eva' subjected to the calcium chloride application in postharvest
Keywords: Malus dosmestica; Refrigeration; Conservation; Malus dosmestica; Refrigeração; Conservação